Analytical agreement between CEDIA immunoassay and HPLC for therapeutic drug monitoring of carbamazepine: a narrative review - Mulki, Munir Alinu; Fitriana, Nariyyah; Ilmi, Yuniar Fathil; Utami, Marsah Rahmawati (Pharmacy Department, Faculty of Health Sciences, Jenderal Soedirman University, Purwokerto, Indonesia, 2025)
speed, simplicity, and cost, but the extent of its agreement with HPLC across diverse clinical contexts requires careful evaluation. Method: This narrative review synthesizes evidence from nine studies identified through Scopus and Google Scholar to assess the analytical agreement and clinical validity of CEDIA and related immunoassay platforms compared to HPLC and advanced chromatographic methods. Results: The reviewed evidence demonstrates strong inter-method correlation, although systematic positive bias in immunoassay results is consistently observed, particularly in patients receiving enzyme-inducing co-medications where carbamazepine-10,11-epoxide accumulation affects antibody cross-reactivity. CEDIA is analytically acceptable for routine CBZ TDM in stable patients on monotherapy. HPLC and LC-MS/MS remain preferable when metabolite quantification, polytherapy monitoring, or precise measurement near therapeutic boundaries is clinically required. Conclusion: Method selection should be guided by the clinical question, patient population characteristics, and available laboratory resources.